Cancer of Unknown Primary - Krämer, Alwin; Löffler, Harald (Springer International Publishing : Imprint: Springer, 2016)
This book presents an up-to-date and thorough overview of cancer of unknown primary, encompassing topics ranging from epidemiology, tumor biology, and prognostic factors through to the most recent diagnostic and therapeutic advances. All aspects of management are covered, including radiological, nuclear medicine, and pathological diagnosis, site-specific therapies, platinum-based combination chemotherapy, radiotherapy, and novel targeted treatments. Clear guidance is offered on diagnosis of the tissue of origin by means of gene expression and micro-RNA analyses and its therapeutic implications. Detailed directions are also provided on the identification of subsets of patients with a more favorable prognosis, in whom specific treatment offers the chance of long-term survival or even cure. Readers will find Cancer of Unknown Primary to be an ideal source of practically oriented information that will assist in delivery of the best possible care for patients with this challenging diagnosis.  .